Common-mode voltage reduction for inverters connected in parallel using an mpc method with subdivided voltage vectors - Park, Joon Young; Sin, Jiook; Bak, Yeongsu; Park, Sung Min; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2018)
This paper presents a model predictive control (MPC) method to reduce the common-mode voltage (CMV) for inverters connected in parallel, which increase the capacity of energy storage systems (ESSs). The proposed method is based on subdivided voltage vectors, and the resulting algorithm can be applied to control the inverters. Furthermore, we use more voltage vectors than the conventional MPC algorithm; consequently, the quality of grid currents is improved. Several methods were proposed in order to reduce the CMV appearing during operation and its adverse effects. However, those methods have shown to increase the total harmonic distortion of the grid currents. Our method, however, aims to both avoid this drawback and effectively reduce the CMV. By employing phase difference in the carrier signals to control each inverter, we successfully reduced the CMV for inverters connected in parallel, thus outperforming similar methods. In fact, the validity of the proposed method was verified by simulations and experimental results.
Keywords: Capacity of energies; Carrier signals; Common mode voltage; Grid connected inverters; Parallel-connected inverters; Phase difference; Phase-shifted carriers; Total harmonic distortion (THD); Common-mode voltage; Grid-connected inverters; Model predictive control; Parallel-connected inverters; Phase-shifted carrier